Understanding First Aid: An Insight into the Knowledge and Attitudes of Different Saudi Medical Specialties towards Emergency Response - Saleh Nashat Al Otaibi; Qamar Khojah; Doaa Al Buraikan; Sarrah Bakr Bin Sadiq Albakri; Munira Mohammed Abdulaziz Al-Hamad; Majdi Mohammed Alosaymi; Rabiah manaa almutiri; Mohammed Abdullah Alsugairan; Mamdouh Mislat Almutairi; Yasir Mofareh Alonaydhil; et al. (International Journal of Medical Toxicology and Legal Medicine, 2024)
First aid is a crucial skill set that can save lives in emergency situations. The knowledge and attitudes of medical professionals towards first aid greatly influence the quality of emergency response and patient outcomes. This paper explores the level of first aid knowledge, attitudes, and practices among different medical specialties in Saudi Arabia, highlighting gaps and areas for improvement. The study examines various first aid scenarios such as burns, choking, drowning, anaphylaxis, and epistaxis, evaluating the preparedness of healthcare professionals in handling these emergencies. The findings emphasize the need for continual first aid training and education to enhance emergency response effectiveness across various medical disciplines.